Kant on Emotion and Value
XIII, 314 p.
Keywords: Distinguished international scholars discuss the connection between emotion and value in Kant's philosophy, from his ethics to his philosophy of mind, aesthetics, religion and politics. Through a mixture of interpretation and critical discussion, this collection demonstrates the continuing relevance of Kant's work to philosophical debates.